PERANAN RETRIBUSI SEKTOR PARIWISATA TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN KOTABARU - ADI PRASETIA; CHAIRUL SA'RONI (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
Adi Prasetia (2018), Role of Retribution of Tourism Sector on Local Own Revenue in Kotabaru Regency.The purpose of this study is to determine the role of retribution in the tourism sector to the Local Revenue in Kotabaru District. In this research using quantitative descriptive method. The type of data used in the form of secondary data about the development of the retribution of the tourism sector to the Local Revenue in Kotabaru District. The results of research can be used by local governments to set policies on the tourism sector to increase the local revenue.Based on the results of this study, it is indicated that the role of tourism retribution is still relatively small with respect to the original regional income in Kotabaru Regency due to the increase in the amount of local revenue with a larger amount.Keywords: Tourism Retribution, Local Original Income